2008
DOI: 10.1007/s00467-008-0800-7
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance therapy with mycophenolate mofetil for children with severe lupus nephritis after low-dose intravenous cyclophosphamide regimen

Abstract: Although recent studies on adults with lupus nephritis indicate that mycophenolate mofetil (MMF) may be effective in maintaining remission for patients who previously received short-term intravenous cyclophosphamide (IVCY) induction therapy, the experience with the new immunosuppressive agent in children with severe lupus nephritis has not been as satisfactory thus far. To assess the efficacy and safety of maintenance therapy with MMF, we prospectively analyzed four patients with biopsy-proven severe lupus nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…However, in our experience by slowly increasing the dose, this main side‐effect can be avoided, although if side‐effects occur, then the total daily dose may be divided into three or four. Maintenance MMF therapy has been advocated in children with SLE and LN after induction therapies with low dose intravenous cyclophosphamide (52).…”
Section: Maintenance Therapiesmentioning
confidence: 99%
“…However, in our experience by slowly increasing the dose, this main side‐effect can be avoided, although if side‐effects occur, then the total daily dose may be divided into three or four. Maintenance MMF therapy has been advocated in children with SLE and LN after induction therapies with low dose intravenous cyclophosphamide (52).…”
Section: Maintenance Therapiesmentioning
confidence: 99%
“…This may be the result of poor compliance of children and adolescents, which may be partially related to adverse gastrointestinal effects of MMF. On the other hand, Fujinaga et al [40] demonstrated that maintenance therapy with MMF appeared satisfactory without flares and adverse effects during follow-up in four children with severe LN. Pecoraro et al [41] reported 14 children with LN who were treated with MMF.…”
Section: Discussionmentioning
confidence: 97%
“…Thereby MMF reduces B-cell proliferation, antibody synthesis and cytotoxic T-cells [23] . There is very little data on the use of MMF in children with lupus nephritis [8,17,18] , the drug is considered off label for this indication in pediatric patients. Against the background of the eff ective use of MMF in maintenance therapy in adults we hypothesized that the drug is similarly eff ective in children and adolescents with SLE.…”
Section: Zusammenfassungmentioning
confidence: 99%